2017
DOI: 10.1002/cctc.201700578
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancies in Reduced Rh/ and Pt/Ceria for Highly Selective and Reactive Reduction of NO into N2 in excess of O2

Abstract: Currently commercial NOx removal (DeNOx) abatement systems for lean‐burn engines exceed regulation limits on the road for NOx emissions. Commercial DeNOx catalysts exhibit poor performance in the selective conversion of NO to N2, especially at high temperature and high gas hourly space velocities (GHSV). In this study, oxygen vacancies of reduced ceria and Pt/ or Rh/ceria are found to be the efficient and selective catalytic sites for NO reduction to N2. Even at low concentrations, NO can compete with an exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
(7 reference statements)
1
10
0
Order By: Relevance
“…were co-fed over C 3 H 6 reduced Rh/CLZ at 450°C. 21 The current study presented in Fig. 4A suggested that N 2 O was comparably reactive towards ceria oxygen vacancies as NO did, and therefore, N 2 O was a more reactive and competitive reactant towards the oxygen vacancies as compared to O 2 .…”
Section: Catalysis Science and Technology Papermentioning
confidence: 54%
See 4 more Smart Citations
“…were co-fed over C 3 H 6 reduced Rh/CLZ at 450°C. 21 The current study presented in Fig. 4A suggested that N 2 O was comparably reactive towards ceria oxygen vacancies as NO did, and therefore, N 2 O was a more reactive and competitive reactant towards the oxygen vacancies as compared to O 2 .…”
Section: Catalysis Science and Technology Papermentioning
confidence: 54%
“…Characterization details of the CLZ support and Rh/CLZ catalyst were reported in detail elsewhere. [16][17][18][19][20][21] In brief, a 0.5 wt% Rh loading was confirmed by ICP-OES (0.0486 mmol g cat…”
Section: Structure Composition and Texture Propertiesmentioning
confidence: 97%
See 3 more Smart Citations